Penerapan KNN Penentuan Pelanggan Baru PDAM dan Clustering K- Means Berdasarkan Wilayah - Mutammimul Ula; Muthmainnah; Ridha Maulana; Veri Ilhadi (E-Jurnal Universitas Samudra, 2023)
The Regional Drinking Water Company (PDAM) Tirta Gunung Pase is a company that distributes and provides drinking water services for the entire region of Lhokseumawe and North Aceh. This research aims to find new customers by determining new pairs and grouping each area in determining clusters in each region. This makes it easier for leaders to view collections by customer ID and the number of household group usage. The research methodology is to collect data at PDAM Tirta Mon Pase, then look at the classification with the KNN model and group it with the K-Means method. A final result is a group of regular customers and non-permanent customers with the variable customer id, house class, and several occupants of the house, and the respective values are seen from UA with a value of 5, RB value of 4, RC value 3, RD value two and SB value 1 with test data using 15 samples. The results of testing the KNN model by entering the customer id 25768, occupants of houses in groups 5 and 4 are included in the class 2 classification. Meanwhile, the customer id is 41162 with the results of group 4 classification and class 1 occupants 3 class 1. Kmeans clustering results for households, businesses and industrial companies. K-Result, while the results of the K-means method contained three clusters which showed that cluster 1 was 46.07%, cluster 2 was 39.79%, and cluster 3 was 14.13%.